Landing Gear Ground Load Measurement and Verification Test for a Large Passenger Jet. (2015) - Xiangjun, Kong; Ningning, Le; Chunsheng, Li; Xianbo, Xiao; Bo, Lin; Bing, Xu
Abstract: Engineered Material Arresting System (EMAS) could be constructed in runway end safety area to arrest an overrun aircraft. EMAS bed is the main part of EMAS and consists of the EMAS material, such as foam concrete. EMAS and its design method should be verified by actual aircraft test. A large passenger jet, one main aircraft type of civil aviation should be used in actual aircraft verification test of EMAS. The jet came from an airline operation front line. To minimize the effect of the test on the jet's airworthiness, the landing gears of the jet should not be remove in the measurement system mounting. The jet's motion in EMAS could be analyzed, and the performance requirement of landing gear load measurement system could be studied. Accordingly, landing gear load measurement system and field calibration test method were presented. For the verification of measurement system, the aircraft taxi tests such as taxi brake test, engine ground run up test and a short EMAS bed test had been done with the system. Through analyzing the measured loads of the landing gears, weight of the jet and the limit load of landing gears, the system could be verified. The results show that the load measurement system could satisfy EMAS actual aircraft verification test, and the test and verification method should satisfy other large aircraft landing gear load measurement